2019
DOI: 10.1007/s00259-019-04370-z
|View full text |Cite
|
Sign up to set email alerts
|

What can artificial intelligence teach us about the molecular mechanisms underlying disease?

Abstract: While molecular imaging with positron emission tomography or single-photon emission computed tomography already reports on tumour molecular mechanisms on a macroscopic scale, there is increasing evidence that there are multiple additional features within medical images that can further improve tumour characterization, treatment prediction and prognostication. Early reports have already revealed the power of radiomics to personalize and improve patient management and outcomes. What remains unclear is how these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Radiomic features have also been suggested to predict clinical endpoints such as survival and treatment response, and, to be directly linked to genomic, transcriptomic, or proteomic characteristics (1,2,9). While even individual radiomic features may correlate with genomic data or clinical outcomes, the impact of radiomics is increased when the wealth of information that it provides -typically hundreds of features, a fraction of which will contribute to a disease-specific "radiomic signature"-is processed using machine learning techniques (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomic features have also been suggested to predict clinical endpoints such as survival and treatment response, and, to be directly linked to genomic, transcriptomic, or proteomic characteristics (1,2,9). While even individual radiomic features may correlate with genomic data or clinical outcomes, the impact of radiomics is increased when the wealth of information that it provides -typically hundreds of features, a fraction of which will contribute to a disease-specific "radiomic signature"-is processed using machine learning techniques (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Modern small-animal based anatomical, functional, and molecular imaging research involves a wide range of well-established as well as more experimental imaging modalities, including micro versions of clinical scanners (µCT, µMRI, µPET, µSPECT, µUS), optical coherence tomography (OCT), fluorescence molecular tomography (FMT), bioluminescence imaging (BLI), photoacoustic (PA) and thermoacoustic (TA) imaging, multispectral imaging (MSI), and others [93] , [158] , [159] . The use of deep learning for automated analysis of such imaging data is relatively uncharted territory, but recent studies have reported first applications in translational molecular imaging experiments [160] , [161] , [162] , [163] , [164] .…”
Section: Deep Learning In Biomedical Imagingmentioning
confidence: 99%
“…Radiomics has shown promising results to analyze tumour heterogeneity using different imaging techniques, including artificial intelligence-based machine-learning algorithms [ 22 , 26 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Taking into consideration the “whole tumour volume” assessment across the entire body instead of just a tiny sample from a single site, radiomic analysis might represent a non-invasive prediction approach to identify patients at high risk of relapse; early identification of these patients could allow modification of their therapeutic management to reduce unnecessary toxicity and improve prognosis according to follow-up studies [ 18 , 20 , 37 , 38 ]. There have been other studies on the diagnostic value of radiomics regarding different types of lymphoma and the reproducibility of CT texture parameters [ 31 , 33 , 35 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%